2011
DOI: 10.1029/2010ja015888
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of fluctuations in the cusp diamagnetic cavity

Abstract: [1] We have analyzed Cluster magnetic field and plasma data during high-altitude cusp crossing on 14 February 2003. Cluster encountered a diamagnetic cavity (DMC) during northward interplanetary magnetic field (IMF) conditions, and as IMF rotated southward, the spacecraft reencountered the cavity more at the sunward side. The DMC is characterized by a high level of magnetic field fluctuations and high-energy electrons and protons. Ultralow-frequency turbulence has been suggested as a mechanism to accelerate pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 53 publications
3
37
0
Order By: Relevance
“…Though some observations agree with this gradual character for the inner transitions, for example Niehof et al (2010); Nykyri et al (2011a), others describe a much more rapid transition (Lavraud et al, 2002). This may be partly due to the dynamic nature of the cusp region, for instance Nykyri et al (2011b) have shown that some of the local fluctuations in plasma parameters within the CDC may be attributed to the reaction of the CDC to solar wind changes on relatively short timescales. This gradual transition in the simulation may also be caused by limited resolution (note that the simulation already has a much higher resolution than typical global models) or by physics not contained within our model such as dipole tilt or inherent fluctuations within the solar wind plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Though some observations agree with this gradual character for the inner transitions, for example Niehof et al (2010); Nykyri et al (2011a), others describe a much more rapid transition (Lavraud et al, 2002). This may be partly due to the dynamic nature of the cusp region, for instance Nykyri et al (2011b) have shown that some of the local fluctuations in plasma parameters within the CDC may be attributed to the reaction of the CDC to solar wind changes on relatively short timescales. This gradual transition in the simulation may also be caused by limited resolution (note that the simulation already has a much higher resolution than typical global models) or by physics not contained within our model such as dipole tilt or inherent fluctuations within the solar wind plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Similar structures of depressed magnetic field are also observed in the high-altitude cusps regions of the Earth, as associated with the observations of cusp energetic particles and ULF wave activity (Nykyri et al, 2011). Therefore, if involving open crustal magnetic field, the observation of an extended current sheet and hot diamagnetic region at Mars could represent an analogy to the cusp diamagnetic cavities of the Earth.…”
Section: Summary and Discussionmentioning
confidence: 90%
“…Lower frequency fluctuations of approximately 0.003 Hz (330 s) were found embedded within the magnetic field vectors showing the current sheet rotation (B x and B y component), indicating either temporal changes from the movement of the current sheet position over the spacecraft, or spatial changes as the spacecraft crossed different sides of the current sheet. Nykyri et al (2011) proposed that a similar property observed in diamagnetic cavities at the cusp regions of the Earth's magnetosphere as responsible for accelerating particles.…”
Section: Summary and Discussionmentioning
confidence: 94%
“…The test particle simulation agrees well with the hybrid simulation at the early nonlinear stage; however, there is large deviation in the vortex region at the later nonlinear stage. This anisotropic temperature is likely to driven small-scale kinetic waves (e.g., mirror modes and ion cyclotron waves; Dimmock et al, 2015;Dimmock et al, 2017;Nykyri et al, 2003;Nykyri et al, 2011) and secondary instabilities (e.g., firehose instability). Note in Figure 4, these two simulations have similar 3 ∕ 1 value in the vortex region, meaning this deviation may be attributed to the different magnetic field directions in fluid and hybrid simulations.…”
Section: Resultsmentioning
confidence: 99%